2014
DOI: 10.1016/j.neulet.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin C-terminal hydrolase L1 interacts with choline transporter in cholinergic cells

Abstract: Ubiquitin carboxyl-terminal hydrolase L1 (UCHL1) is a deubiquitinating enzyme, which is highly expressed in neuronal cells. Previous studies have indicated that UCHL1 is involved in cognitive function, neurodegenerative diseases, and neuromuscular junction development. Acetylcholine (Ach) is a critical neurotransmitter in these functions. Yet, the effect of UCHL1 on the cholinergic system has not been reported. In this study, using a cholinergic neuronal cell line, SN56, as an in vitro model, we detected the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…UCHL1 siRNA gene knockdown was performed as described previously[17] with some modifications. Briefly, C2C12 cells were grown in GM to desired confluence.…”
Section: Methodsmentioning
confidence: 99%
“…UCHL1 siRNA gene knockdown was performed as described previously[17] with some modifications. Briefly, C2C12 cells were grown in GM to desired confluence.…”
Section: Methodsmentioning
confidence: 99%
“…Ubiquitination proteolytically cleaves synaptic proteins or interferes with trafficking of such proteins, including the CHT (Buttner et al, 2001;Hartnett et al, 2014;Meyer et al, 1986;Yamada et al, 2012).…”
Section: Elevated Levels Of Poly-ubiquitylated Cht In Stsmentioning
confidence: 99%
“…Ubiquitination can occur in diverse ways, including conjugation to just one residue in its substrate (mono-ubiquitination) or multiple times to this residue, with the initial ubiquitin serving as the target for additional ubiquitination (poly-ubiquitination). Beyond the classical ubiquitin-dependent proteolysis, ubiquitination may interfere with numerous other aspects of the regulation and functions of proteins, such as the intracellular transport of proteins (e.g., Buttner et al, 2001; Schmidt et al, 2021; Lopez-Castejon, 2019; Kwon and Ciechanover, 2017), including of CHTs in vitro (Hartnett et al, 2014; Cuddy et al, 2012; Foot et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ub-mediated degradation of essential enzymes may have particular importance in the central nervous system. Using TUBEs, it was shown that Ub carboxy-terminal hydrolase 1 (UCHL1) antagonizes ubiquitylation of choline transporter (CHT) in a cholinergic neuron model [76]. While K48-linked polyubiquitylation is typically considered to target proteins for degradation, TUBEs identified noncanonical Ub-dependent degradation mechanisms, as K63linked HIF1A ubiquitylation signaling degradation by the ALS, expanding the known roles of Ub in intracellular proteolysis [77].…”
Section: Study Of the Ubiquitylation Of Specific Proteinsmentioning
confidence: 99%